2001
DOI: 10.1177/000841740106800102
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Canadian Occupational Performance Measure as an Outcome of a Pain Management Program

Abstract: The last three decades have seen the emergence of measures to assess the efficacy of pain management programs. Recently there has been interest in measures that assess clients' perceptions of their own performance. The Canadian Occupational Performance Measure (COPM) (Law et al, 1994, 1998) is an individualized measure designed for use by occupational therapists to detect a self-perceived change in occupational performance problems over time. It may be an important extra dimension to assessing the outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 10 publications
5
88
0
Order By: Relevance
“…The results of this study showed that the COPM-P was only weakly to moderately associated with the outcomes of the PDI and We were not able to find support for the construct validity and responsiveness of the COPM-P in this population and setting. Although many authors have explained their results differently, the results of this study are in line with prior studies, finding mostly low or no correlations [17,21,[29][30][31]34,38].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of this study showed that the COPM-P was only weakly to moderately associated with the outcomes of the PDI and We were not able to find support for the construct validity and responsiveness of the COPM-P in this population and setting. Although many authors have explained their results differently, the results of this study are in line with prior studies, finding mostly low or no correlations [17,21,[29][30][31]34,38].…”
Section: Discussionsupporting
confidence: 91%
“…The extent to which pain interfered with daily life significantly reduced as well. Both Persson et al [23] and Carpenter et al [29] revealed a significant improvement of COPM-P after a pain rehabilitation program as well, resembling the program of Reade, supporting the absolute responsiveness of the COPM.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations